First-pass isolation and procedural metrics associated with catheter ablation outcomes for atrial fibrillation: a retrospective cohort study - Zexi Li; Fanghui Li; Xianjin Hu; Aobo Gong; Ying Cao; Bangjiaxin Ren; Wenjie Li; Yifan Zhou; Rui Zeng (Frontiers in Cardiovascular Medicine, 2026)
Background First-pass isolation (FPI) during pulmonary vein isolation (PVI) is an acute procedural endpoint that may reflect the quality of initial lesion delivery and has been proposed as a predictor of durable ablation success. This study aimed to evaluate the association between FPI and post-ablation outcomes, identify factors associated with FPI achievement, and determine whether procedural metrics add prognostic information beyond conventional clinical variables in atrial fibrillation (AF) patients. Methods This retrospective cohort study included 313 AF patients undergoing first-time radiofrequency catheter ablation between August 2023 and January 2025. Patients were classified into two groups: those without FPI in either ipsilateral PVs (NEITHER, n = 60) and those with FPI in at least one of the two ipsilateral PVs (IFPI, n = 253). For additional analyses, the IFPI group was further classified into patients with FPI in both ipsilateral PVs (BOTH, n = 151) and those with FPI in either ipsilateral PVs (EITHER, n = 102). Procedural metrics for each PV circle, including C3-FOT ratio and gap number, were assessed using the AIFV system (an analytic platform analyzing raw CARTO3 data). The clinical endpoint was freedom from documented atrial arrhythmias after the blanking period, including AF, atrial tachycardia, or atrial flutter lasting longer than 30 s during follow-up. Results FPI was achieved in 64.5% (404/626) of ipsilateral PV circles. Higher C3-FOT ratio was independently associated with greater FPI achievement, whereas right-sided PV location and higher gap number were associated with reduced FPI achievement. During a median follow-up of 21.1 months, 81 patients (25.9%) experienced recurrence. The NEITHER group had lower recurrence-free survival than the IFPI group (log-rank P = 0.013) and a higher adjusted recurrence risk (HR: 1.680; 95% CI: 1.021–2.763; P = 0.041). Failure to achieve C3-FOT qualification in both PV sides and total gap burden >2 were also independently associated with recurrence. C3-FOT qualification appeared to provide more prognostic information than FPI beyond traditional clinical factors. Conclusions IFPI was independently associated with a lower risk of atrial arrhythmia recurrence, while FPI achievement was related to favorable procedural characteristics including lower gap burden and higher C3-FOT ratio.